A New Approach to Blood Parameters in Dogs with Hemorrhagic Enteritis - Arslan, Handan Hilal; Guzel, Murat; Meral, Yucel; Dalgin, Duygu; Gokalp, Guvenc; Ozcan, Umit (Acta Scientiae Veterinariae, 2017)
Background: Some blood parameters have diagnostic and prognostic importance for the infections in human medicine. However, there is insufficient research regarding the importance of blood parameters and their correlations in veterinary medicine. Increased blood cell distribution width (RDW) and platelet activity can link with the important inflammatory markers. The main objective of the present study was the evaluation of the relationship among some important blood parameters namely RDW, platelet count (PLT), platelet distribution width (PDW), mean platelet volume (MPV), plateletcrit (PCT), their potential usage in the diagnosis and determination of the clinical severity in dogs with hemorrhagic enteritis. Materials, Methods & Results: In this study, the case records of 29 dogs with hemorrhagic enteritis were evaluated and the records of 10 healthy dogs were used as controls. The animals of the study group were presented at the Ondokuz Mayis University, Veterinary Internal Medicine Clinic. The complete blood count (CBC), which includes the total WBC, RBC, hematocrit (HCT), hemoglobin concentration (Hgb), MCV, mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), RDW, PLT, MPV, PCT, and PDW, was determined. Significant positive correlations between RDW and RBC, HCT, MCHC, PLT and PDW, and a negative correlation with MCV, were determined. PDW was positively correlated with the lymphocyte count, MCHC and RDW, and negatively correlated with PCT. PLT was negatively correlated with MCV and MPV and positively correlated with RBC and RDW. In addition, MPV was positively correlated with MCV and MCH, and negatively correlated with PLT. Furthermore, there were significant differences between the granulocyte, WBC, HCT, RDW and PDW values (P < 0.001) and monocyte count, Hgb and MCV (P < 0.05), of the study and control groups. Discussion: Acute hemorrhagic enteritis has various causes in dogs such as idiopathic hemorrhagic gastroenteritis and a number of viral, bacterial and parasitic agents. Hematological and biochemical parameters are not specific to enteric diseases, but these paremeters can provide clinically helpful information for differential diagnosis, response to treatment, and prognosis. In this frame, the evaluation of MCV and RDW in combination, and the determination of the mean red cell size and the extent of heterogeneity of the red cell population, can be especially useful to the diagnosis of different red blood cell disorders. In the present study, differences in RDW and MCV values were statistically significant between the study and control groups (P < 0.05). Increased RDW and decreased MCV can be good indicators of hemorragic diseases and in the present study, in addition to these findings, decreased Hgb and Hct confirmed anemia in dogs with hemorrhagic enteritis. The other key findings of this study were statistically significant relationships between RDW, PLT and PDW, which could be important indicators of inflammation in dogs with hemorrhagic enteritis. These parameters should be evaluated carefully in clinical cases of hemorrhagic enteritis. However, due to nature of retrospective studies, there were some limitations (the lack of another control group of dogs suffering from other hemorrhagic diseases) lack of serial measurements of the blood parameters and further studies should be carried out on dogs with hemorrhagic enteritis for a more detailed evaluation and confirmation of the findings of this study.